Evaluation of the application of wild yeasts in inhibiting germination of ochratoxin-producing Fungi during coffee fermentation process - Tsung-Yu Liu; Wei-Hsuan Hsu; Bao-Hong Lee (Food Chemistry: X)
Specialty coffee, typically lightly roasted, is valued for its unique fruity aroma. However, the fermentation process poses a risk of contamination with ochratoxin-producing fungi. This study aimed to select wild yeast strains capable of contributing distinctive flavor profiles while inhibiting the growth of ochratoxin-producing fungi. Coffee pulp served as a substrate to simulate yeast growth during coffee fermentation, allowing for the evaluation of yeast metabolites potential to inhibit spore germination in ochratoxin-producing fungi (Aspergillus niger). The findings demonstrated that the Saccharomyces cerevisiae strain effectively inhibited spore germination in A. niger. High-performance liquid chromatography (HPLC) analysis indicated that citric acid is likely the primary organic acid responsible for inhibiting A. niger spore germination. These results suggested that S. cerevisiae has potential applications in enhancing the food safety of coffee.